Physical activity during pregnancy: Benefits and global recommendations - Rovčanin Marija; Vujčić Isidora; Janković Svetlana (Medicinski Podmladak, 2023)
Physical activity (PA) has a crucial role in the prevention of noncommunicable diseases on a global scale. Regular PA leads to the enhancement of numerous health aspects by improving numerous physiological, metabolic, and psychological parameters. It is one of the crucial preconditions for much of human health needs, particularly for the reproductive-aged population and pregnant women. During pregnancy, PA has a beneficial impact not only on the well-being of the pregnant mother but also on the health of the baby. There are presently no official national guidelines regarding PA during pregnancy in Serbia, so we advocate for and adhere to the worldwide norms. The widespread agreement is that every woman, excluding those with certain clinical or antenatal contraindications, should engage in PA throughout their pregnancy. While formatting the recommendations, particular attention was placed on the duration of exercising, the number of days per week an activity is performed, a subjective measure of how hard PA feels to a person while doing it (subject perceived exertion), the sort of PA that is suggested, but also those that should be avoided, as well as techniques for supervision with clearly defined indicators that indicate the need to discontinue a certain activity. It has not been effectively established via initiatives meant to enhance the general health of a population of Serbian pregnant women, one of the most susceptible demographic groups. Moreover, in Serbia, there have not been enough studies on the impacts and advantages of exercising during gestation, and neither is there any consensus on the best way to counsel expectant mothers during their pregnancies. Future research should be required to design and promote PA programs for expectant mothers, in an effort to prevent pregnancy difficulties, by outlining the significance and advantages of leading an active lifestyle during pregnancy and keeping track of attitudes and behaviors linked to health. Regarding the physiological changes associated with pregnancy, modest physical exercise during gestation should be promoted and strongly recommended.